(untitled) (Research, Society and Development, 2025)
The current scenario in strawberry cultivation is the adoption of the off-ground method in substrate, which reduces the relevance of the planting period in the transplanting process. This study aimed to carry out an agronomic characterization of strawberry genotypes grown out of the ground, under an organic production system. An experimental design with subdivided plots was used for each pair of genotypes, where the plots represented the genotypes themselves and the subplots represented the months of evaluation. Each genotype was evaluated in three replicates, totaling 18 plants in each. The evaluations included phenological aspects, commercial classification, coloring, plant characterization, and production aspects. The data was analyzed using variance, with differences between means evaluated using the Tukey test at 5% probability. Throughout the evaluations, DN3 outperformed DN6 in terms of diameter, number of fruits, production and chlorophyll content, while being phenologically later. Among the short-day genotypes, DC10 stood out with greater diameter, chlorophyll content and production at harvest, demonstrating precocity in relation to DC01. However, due to the late planting, the production of the short-day genotypes was lower than expected, revealing a more significant impact of this practice.